Missed opportunity for alcohol use disorder screening and management in primary health care facilities in northern rural Tanzania: a cross-sectional survey - Dorothy Mushi; Candida Moshiro; Charlotte Hanlon; Joel M. Francis; Solomon Teferra (BMC, 2022)
Abstract Objective The study aimed to identify the missed opportunity for detection and management of alcohol use disorder by primary health care workers. Design A cross-sectional survey Setting Outpatient services in the six governmental primary health care facilities in Moshi district council in Tanzania. Participants A total of 1604 adults were screened for alcohol use disorder (AUD) using the Alcohol Use Disorder Identification Test (AUDIT). Participants scoring 8 or above then provided details about their help-seeking behavior and barriers to seeking care. Participants' records were reviewed to assess the screening and management of AUD. Results In the last 12 months, 60.7% reported alcohol use, and heavy episodic drinking (HED) was reported by 37.3%. AUD (AUDIT ≥ 8) was present in 23.9%. Males were more likely to have HED (aPR = 1.43;95% CI:1.3 to 1.4) or AUD (aPR = 2.9; 95% CI 1.9 to 4.2). Both HED and AUD increased with age. Only one participant (0.3%) had documented AUD screening and management. Only 5% of participants screening positive for AUD had sought help. Reasons for not seeking care were thinking that the problem would get better by itself (55.0%), wanting to handle the problem alone (42.0%), or not being bothered by the problem (40.0%). Conclusion While reported alcohol use, HED, and AUD are common among patients presenting to primary healthcare facilities in northern Tanzania, help-seeking behavior and detection are very low. Not screening for AUD in primary health care is a missed opportunity for early detection and management. There is an urgent need to develop interventions to increase the detection of AUD by health care providers, while also addressing help-seeking behavior and barriers to seeking care.